Factors Associated With Low Self-Esteem Among Patients With Hematologic Malignancies: A Cross-Sectional Study - Yu, Junye; Dong, Huan; Wu, Qi; Yang, Ya; Pi, Hongying (Frontiers in Psychiatry, 2021)
The present study aimed to explore the self-esteem level of patients with hematology malignancies and the associated factors. In this cross-sectional study, we screened patients with hematologic malignancies treated in the Department of Hematology of Aerospace Center Hospital between November 2019 and June 2020. We included 157 eligible patients by convenience sampling. The participants completed questionnaires covering demographic characteristics, loneliness, the coping styles, hope, five personality traits, and self-esteem level. We applied t-test, analysis of variance, simple linear regression, and multiple stepwise regression to explore the factors associated with patients’ self-esteem. The mean self-esteem score of hematology tumor patients was 26.86±2.34, which was lower than the national norm (P<0.01). The multiple stepwise regression analysis identified maintaining close relationships with others, conscientiousness, extroversion, agreeableness, and positive coping style as factors independently associated with the self-esteem of hematology tumor patients. Patients with hematologic malignancies experience low self-esteem. Factors including maintaining close relationships with others, conscientiousness, extraversion, agreeableness, and active coping style were found to be independently associated with the self-esteem level of these patients. For patients with hematologic malignancies, health providers should apply patient-centered and targeted interventions to improve patients’ self-esteem, reduce adverse psychological emotions, and improve their quality of life.